2013
DOI: 10.1017/s0047279413000597
|View full text |Cite
|
Sign up to set email alerts
|

The Liberalisation of the German Social Model: Public–Private Pension Reform in Germany since 2001

Abstract: Some commentators view reforms to the German political economy since the 1990s as constituting a broad liberalisation of a previously coordinated market economy (e.g., Streeck, 2009). Others argue that by maintaining protection for core workers the reforms represent a dualisation rather than liberalisation (e.g., Palier and Thelen, 2010). This debate has paid little attention to public-private pension reform since 2001. This paper argues that pensions have been a crucial component of the German social model si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…More generally, there is scope for research that compares and explains pension system dynamics in the different worlds of welfare. This paper has shown liberal pension systems to be more resilient than expected; the literature on conservative and social democratic systems generally shows the contrary, with dualizing (e.g., Emmenegger et al, ) or liberalizing (Bridgen & Meyer, ) processes evident. Overall, it has been suggested that we are witnessing a “middle‐of‐the‐road convergence” in welfare states (Achterberg & Yerkes, ; see also Overbye, ) rather than the neo‐liberal one predicted by the globalization thesis (see Pierson, , , p. 81).…”
Section: Discussionmentioning
confidence: 67%
“…More generally, there is scope for research that compares and explains pension system dynamics in the different worlds of welfare. This paper has shown liberal pension systems to be more resilient than expected; the literature on conservative and social democratic systems generally shows the contrary, with dualizing (e.g., Emmenegger et al, ) or liberalizing (Bridgen & Meyer, ) processes evident. Overall, it has been suggested that we are witnessing a “middle‐of‐the‐road convergence” in welfare states (Achterberg & Yerkes, ; see also Overbye, ) rather than the neo‐liberal one predicted by the globalization thesis (see Pierson, , , p. 81).…”
Section: Discussionmentioning
confidence: 67%
“…Traditionally, the German pension system mainly rested on the public pension pillar, whichbased on social-insurance contributionsused to be directed at maintaining the standard of living during old age. Those main features were basically kept until the new millennium (Bridgen & Meyer, 2014). Similar to other countries (Béland, 2019;Hagelund & Grødem, 2019, both in this Special Issue), however, during the 1990s Germany's public pension system came increasingly under reform pressure in face of population ageing, high unemployment rates, and the financial burden of reunification.…”
Section: The Argumentative Construction Of Reform Narratives In Germamentioning
confidence: 73%
“…In Germany in 2001 radical retrenchment provided a direct solution to the problem that already significant pension contributions were projected to rise over the next decades; at the same time the cuts did not affect anyone immediately, but they would be phased in over decades. The red-green coalition government could thus claim the credit for a reform whose full impact future governments will need to confront (Bridgen and Meyer 2014). In Sweden in the context of a deep recession at the beginning of the 1990s and an ageing society actors across the political spectrum agreed that a structural pension reform was needed, which would cut costs and tie outcomes more strongly to market performance and demographic change, while keeping a minimum level for those on low incomes (Anderson und Meyer 2003;Belfrage and Ryner 2009, p. 270-273;Belfrage 2015).…”
Section: The Literature In the Light Of Pension Promisesmentioning
confidence: 99%